2008
DOI: 10.1209/0295-5075/82/54002
|View full text |Cite
|
Sign up to set email alerts
|

Observation of ultra-narrow electromagnetically induced transparency and slow light using purely electronic spins in a hot atomic vapor

Abstract: Electromagnetically induced transparency (EIT) is observed in gaseous 4 He at room temperature. Ultra-narrow (less than 10 kHz) EIT windows are obtained for the first time for purely electronic spins in the presence of Doppler broadening. The positive role of collisions is emphasized through measurements of the power dependence of the EIT resonance. Measurement of slow light opens up possible ways to applications.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 40 publications
10
53
0
Order By: Relevance
“…This value is consistent with measurements of the evolution of the width of the EIT transparency window with respect to the coupling power [21], that give Γ R /2π 14 kHz. This is broader than the few kHz that we had previously recorded [25], as expected from the fact that we now have reduced beam diameters down to 3 mm, thus decreasing the transit time.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This value is consistent with measurements of the evolution of the width of the EIT transparency window with respect to the coupling power [21], that give Γ R /2π 14 kHz. This is broader than the few kHz that we had previously recorded [25], as expected from the fact that we now have reduced beam diameters down to 3 mm, thus decreasing the transit time.…”
supporting
confidence: 90%
“…It has previously been shown that it can exhibit very narrow EIT resonances with a kilohertz linewidth, leading to dramatic changes in the group velocity of the probe beam [21,22]. Such results are extremely promising when it comes to storage experiments.…”
mentioning
confidence: 95%
“…Here the optical coherence decay rate Γ is replaced by the Doppler width [18,19]. One roughly observes three different regimes.…”
mentioning
confidence: 99%
“…Metastable helium is well known to exhibit a pure three-level Λ system when excited at 1.083 µm between the 2 3 S 1 and 2 3 P 1 energy levels using circularly polarized light. In these conditions, narrow EIT windows can be obtained [17]. Light The frequencies ω C,P and Rabi frequencies Ω C,P of our coupling and probe beams are driven by two acoustooptic modulators (AOs).…”
mentioning
confidence: 99%
“…The fact that the finesse of the cavity in the presence of EIT (black curve of Fig. 2) is smaller than without the atoms is due to the residual absorption of the atoms [17,18]. In order to measure τ cav for this cavity, one slowly scans its length and turns off the probe beam using AO 1 when it reaches resonance.…”
mentioning
confidence: 99%